The Use of Animal Models to Decipher Physiological and Neurobiological Alterations of Anorexia Nervosa Patients - Méquinion, Mathieu; Chauveau, Christophe; Viltart, Odile (Frontiers in Endocrinology, 2015)
Extensive studies were performed to decipher the mechanisms regulating feeding due to the worldwide obesity pandemy and its complications. The data obtained might be adapted to another disorder related to alteration of food intake, the restrictive anorexia nervosa. This multifactorial disease with a complex and unknown etiology is considered as an awful eating disorder since the chronic refusal to eat leads to severe and sometimes irreversible complications for the whole organism, until death. There is an urgent need to better understand the different aspects of the disease to develop novel approaches complementary to the usual psychological therapies. For this purpose, the use of pertinent animal models becomes a necessity. We present here the various rodent models described in the literature that might be used to dissect central and peripheral mechanisms involved in the adaptation to deficient energy supplies and/or the maintenance of physiological alterations on the long term. Data obtained from the spontaneous or engineered genetic models permit to better apprehend the implication of one signaling system (hormone, neuropeptides, neurotransmitter) in the development of several symptoms observed in anorexia nervosa. As example, mutations in the ghrelin, serotonin, dopamine pathways lead to alterations that mimic the phenotype, but compensatory mechanisms often occur rendering necessary the used of more selective gene strategies. Until now, environmental animal models based on one or several inducing factors like diet restriction, stress or physical activity mimicked more extensively central and peripheral alterations decribed in anorexia nervosa. They bring significant data on feeding behavior, energy expenditure and central circuit alterations. Animal models are described and criticized on the basis of the criteria of validity for anorexia nervosa.